A 2-year intercomparison of the WAM-Cycle4 and the WAVEWATCH-III wave models implemented within the Mediterranean Sea - KORRES, G.; PAPADOPOULOS, A.; KATSAFADOS, P.; BALLAS, D.; PERIVOLIOTIS, L.; NITTIS, K. (Mediterranean Marine Science, 2011)
In this work we present the implementation of a wave forecast/hindcast system for the Mediterranean Sea at a 1/10º horizontal resolution and we show a first assessment of its performance by inter-comparing model results to observational data time series at selected points for the period 2000-2001. The system which is part of the POSEIDON-II operational system includes the WAM – Cycle4 and the WAVEWATCH-III wave forecast models (implemented within the same region) one way coupled with the non-hydrostatic version of the ETA atmospheric model which provides at 3-hour intervals the necessary wind velocity fields to the wave models. The same system but based on the WAM-Cycle4 wave model, has been used in the past for the production of the Aegean Sea wind and wave Atlas. Overall, the inter-comparison shows that both wave models are rather skilful in predicting the integral wave parameters with significant wave height skill scores in the range 0.85-0.90 and mean period scores in the range 0.77-0.83. It is also evident that WAM model has a tendency to overestimate mean wave periods while the opposite is true for WAVEWATCH-III model. Differences between the two models simulated spectra exist along the main passage of cyclonic systems over the Mediterranean Sea while in the wind seas dominated areas of the basin (the Aegean Sea for example) the two models show almost the same behavior.